Sleeping beauty: favourite tales - Baxter, Nicola; Perrault, Charles (Ladybird Loughborough, 1994)
The former "Well Loved Tales" series have been redesigned with brighter inks and coated paper to enhance the appeal of these fairy tales to young children. They are all intended for one level of readability and are considered ideal bedtime stories. This is the story of "Sleeping Beauty".